2018
DOI: 10.3389/fimmu.2018.01757
|View full text |Cite
|
Sign up to set email alerts
|

CL-L1 and CL-K1 Exhibit Widespread Tissue Distribution With High and Co-Localized Expression in Secretory Epithelia and Mucosa

Abstract: Collectin liver 1 (CL-L1, alias collectin 10) and collectin kidney 1 (CL-K1, alias collectin 11) are oligomeric pattern recognition molecules associated with the complement system, and mutations in either of their genes may lead to deficiency and developmental defects. The two collectins are reportedly localized and synthesized in the liver, kidneys, and adrenals, and can be found in the circulation as heteromeric complexes (CL-LK), which upon binding to microbial high mannose-like glycoconjugates activates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…7,8 The classical and lectin pathways begin with pattern recognition molecules (PRMs) that recognize altered cell surface or foreign ligands. 13,14 CL-11 is expressed in a number of organs 15 and within the kidney it is predominantly expressed in the renal tubules but is also present in the glomerular mesangium and epithelium. The emphasis of our study is on Collectin-11 (CL-11), a lectin pathway PRM known to have significant expression throughout major organs, 11,12 and a major focus of recent work in our lab.…”
mentioning
confidence: 99%
“…7,8 The classical and lectin pathways begin with pattern recognition molecules (PRMs) that recognize altered cell surface or foreign ligands. 13,14 CL-11 is expressed in a number of organs 15 and within the kidney it is predominantly expressed in the renal tubules but is also present in the glomerular mesangium and epithelium. The emphasis of our study is on Collectin-11 (CL-11), a lectin pathway PRM known to have significant expression throughout major organs, 11,12 and a major focus of recent work in our lab.…”
mentioning
confidence: 99%
“…Similar low pH, low calcium conditions result from infection-induced local inflammation ( 42 ). Immunohistochemical analyses have revealed that CL-11 is expressed (among others) in the stomach and the intestines ( 11 ). At this stage we can only conjecture whether the calcium-independent zymosan interaction may be of biological relevance in acidic environments with low calcium availability.…”
Section: Discussionmentioning
confidence: 99%
“…CL-11 deficiency is one of the causes of the 3MC (Malpuech, Michels, Mingarelli, and Carnevale) syndrome ( 3 , 10 ), a congenital disorder associated with craniofacial dysmorphism, mental retardation, growth deficiency, and physical abnormalities. CL-11 is expressed ubiquitously in the body and it appears to play an important role in maintaining homeostasis in the tissue of expression ( 1 , 11 ). During embryonic development, CL-11 is highly expressed in the craniofacial cartilage and vertebral bodies, where together with MASP-3 and CL-10, may act as a guidance cue for neural crest cell migration ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…A total of three polypeptide chains of (two of CL-K1 and one of CL-L1) join to form a heteromeric subunit, which may further oligomerize into structures ranging from dimer to hexamer (acc. to Hansen et al, 2018[41]).…”
mentioning
confidence: 92%